Effects of Project-Based Learning with Project Guide E-book on Critical Thinking and Metacognitive Skills: A Case from Undergraduate Biology Students in Genetic 1 Course - Hikmah Buroidah; Siti Zubaidah; Susriyati Mahanal (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Critical thinking skills bears a fundamental role in students’ thinking process and achievement. Meanwhile, the cornerstone of critical thinking is a metacognitive activity that has a substantial function in measuring and evaluating the obtained information, as well as learning from the experience. This study aims to examine students’ critical thinking and metacognitive skills before and after they participate in the PBL classroom using a project guide e-book for the genetic one course. The student’s critical thinking skills were assessed using written tests using open-ended question items. Further, the obtained scores were analyzed using paired t-test. The data analysis suggested an increase in students’ metacognitive and critical thinking skills after they attended the PBL class using the PBL-based project guide e-book for genetic 1. This increase was shown from the 0.000< α (α = 0,05) significance score of paired t-test. Thus, the PBL-based project guide e-book for the genetic 1 course is capable of enhancing students’ metacognitive and critical thinking skills.